Becoming A Whole Human: Qur'an Perspective Letter At Tiin: 4 And Letter Ad Dzariyat: 56 - Cindy Fatika Sary; Anisya Astanti Utomo; Didik Himmawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this research is to understand in more detail the nature of humans, the position of humans, human responsibilities, the characteristics of humans in the Qur'an, the purpose of human life in the Qur'an and the process of creating humans as creatures of Allah Swt. So that it can be known that humans are creatures of Allah Swt. which consists of a spirit and body equipped with potential and advantages compared to Allah Swt. creatures. others, namely the heart, mind and body. The author uses qualitative research methods, so this research will produce information that provides a comprehensive and clear picture of how to be a complete human being. From research conducted by the author with the title